Peran Mediasi Strength Use antara Strength-Based Parenting dan Subjective Well-Being pada Masa Emerging Adulthood - Vida Handayani; Marissa Chitra Sulastra (Humanitas (Jurnal Psikologi), 2025)
This study aimed to examine the mediating role of Strength Use in the relationship between Strength-Based Parenting and subjective well-being during emerging adulthood. Subjective well-being was assessed through Life Satisfaction and the Scale of Positive and Negative Experience (SPANE). This quantitative survey-based research involved 459 emerging adult respondents aged 18-24 years, predominantly female (81.9%) and with a high school education (64.05%). Data were collected using online questionnaires and analyzed with path analysis using the bootstrapping method. The results indicated that Strength-Based Parenting directly and significantly influenced Life Satisfaction (β = 0.152, p < .001) and SPANE (β = 0.215, p < .001). Strength Use also significantly affected Life Satisfaction (β = 0.233, p < .001) and SPANE (β = 0.221, p < .001). Furthermore, Strength Use significantly mediated the relationship between Strength-Based Parenting and Life Satisfaction (indirect effect = 0.106, p < .001) and SPANE (indirect effect = 0.101, p < .001). This suggests a complementary mediation, where Strength-Based Parenting still has a significant direct effect, but part of its influence is also mediated by Strength Use. These findings underscore the importance of Strength-Based Parenting and the role of Strength Use in promoting Subjective Well-Being among emerging adulthood.